Development of IoT Based Real Time Cardiac State Monitoring System - Akter, Sumaya; Akter, Sumaya; Subha, Nishat; Subha, Nishat; Tara, Kusum; Tara, Kusum; ur Rahman, Habib; ur Rahman, Habib; Sarkar, Ajay Krishno; Sarkar, Ajay Krishno (Proceedings (IEEE Region 10 Symposium. Online), 2020)
Cardiovascular disease (CVD) is one of the leading causes of death since the last few decades in overpopulated countries like Bangladesh. CVDs can be monitored by detecting and analyzing the Electrocardiography (ECG) signal of heart. In this paper, an IoT based real time cardiac state remote monitoring system has been proposed. At first, heart rate sensor takes lead I ECG signal and transmits the signal to the database server. Then MATLAB based GUI window is designed for automatic detection of cardiac state. Power spectral density (PSD) with the variation of frequency and heart rate for diseased subject differ much from healthy subjects. The results are compared with clinical report obtained from medical. The result provides more than 95 percent accuracy. This cardiac state monitoring system enables remote care and generally gives patients more control over their lives and treatment as well.